Evaluasi Penerapan Indikator Tuberkulosis Paru dalam Program Indonesia Sehat dengan Pendekatan Keluarga (PIS-PK) dengan Model CIPP (Studi pada Puskesmas Pudakpayung) - Azzahra, Annisa Shafa (Jurnal Riset Kesehatan Masyarakat, 2025)
Pudakpayung Public Health Center recorded the lowest pulmonary tuberculosis (TB) indicator achievement within Program Indonesia Sehat dengan Pendekatan Keluarga (PIS-PK) in the Banyumanik District of Semarang City, at only 36.36%, and also had the lowest IKS in the city. This study aimed to evaluate the implementation of the pulmonary TB indicator under the PIS-PK at Pudakpayung Public Health Center. The research was conducted from May 2024 to July 2025. This research was a qualitative study using a descriptive approach through in-depth interviews, observations, and literature review. Participants were selected using purposive sampling. The evaluation was conducted using the CIPP (Context, Input, Process, Product) model by Daniel L. Stufflebeam, which was modified in accordance with Permenkes No. 39 of 2016. Results of this study revealed the absence of technical Standard Operating Procedures (SOPs) for home visit activities, insufficient funding, a high workload among health personnel, insufficient IT skills in operating Aplikasi Keluarga Sehat, and inadequate understanding of operational definitions for identifying TB symptoms. Additionally, educational media such as Pinkesga were not consistently available and there was no integrated information system between the PIS-PK and TB program. Suboptimal maintenance and utilization of electronic tablets and inadequate health education and communication efforts to support TB treatment adherence were also noted. These factors collectively contributed to the underachievement of the TB indicator targets. Overall, the implementation of the pulmonary TB indicator within the PIS-PK at the Pudakpayung Public Health Center was found to be suboptimal and requires further improvement to comply with the standards outlined in Permenkes No. 39 of 2016.